Innovative Approaches in Social Education for Student Engagement - Atin Priatin Munawaroh (JELIM : Journal of Education, Language, Social and Management, 2026)
This study aims to examine the use of innovative approaches in social education and their impact on student engagement in the learning process. In response to the demands of 21st-century education, traditional teaching methods are no longer sufficient to actively involve students. Therefore, innovative, student-centered strategies are needed to create more meaningful and interactive learning experiences. This research employed a qualitative approach involving teachers and students in secondary schools. Participants were selected through purposive sampling based on their involvement in social education learning. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data were analyzed using thematic analysis to identify patterns related to teaching strategies, student engagement, and implementation challenges. The findings reveal that innovative approaches such as project-based learning, collaborative learning, role-playing, and the use of digital media significantly enhance student engagement. Students demonstrated higher levels of participation, motivation, and interaction during the learning process. In addition, these approaches contributed to the development of critical thinking, communication, and collaboration skills. Teachers played a key role in facilitating active learning and creating a supportive classroom environment. However, challenges such as limited resources, lack of training, and time constraints were identified as barriers to effective implementation. In conclusion, innovative approaches in social education are effective in promoting student engagement and improving learning outcomes. It is recommended that educational institutions support teachers through training and provide adequate resources to ensure the successful implementation of these approaches.